Nativevarieties, an opportunity for Chilean pisco - Pszczólkowski, Philippo; Lacoste, Pablo (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2016)
A critical analysis of the varieties used in the production of pisco in Chile is done, making some comparisons with other South American spirits such as pisco of Peru and Bolivia singani. It is found that in the Chilean case, 99.7% of the surface corresponds toMuscat of Alexandria (14.0%) and native varieties (85.7%), with low percentage of varieties associated to the French paradigm (0,21%). It aims to define the Chilean pisco as an Andean spirit made from native and historical varieties of Spanish colony, which would position the Chilean pisco to the Andean territory by traditionally and genetic material.